Study influence of Salinomycin and Anticoccidial Vaccine on Pathological changes in intestine of Broiler Chickens experimental infected with Eimeria spp. - Kalef, Dalia Ahmed (The Iraqi Journal of Veterinary Medicine, 2008)
To conduct the influence of salinomycin & anticoccidial vaccine onpathological changes in intestine of broiler chickens experimentalinfected with Eimeria spp. By using 40 broiler chicks divided randomlyto four groups( 10 chicks of each group ) First group vaccinated withanticoccidial vaccine (coccivac) at 8 days of age in drinking water whilethe second group feeded salinomycin in concentration 60ppm from oneday old ,the third group left non vaccinated nor given salinomycin as acontrol group at(26 days )of age chicks in that three groups infected withdifferent species of Eimeria spp .with high dose (744x74³) Oocyst /chickby group inoculation & the fourth group consider negative control notvaccinated or treated .At (33 days)of chicks age all the chicks were killedfor measuring lesion score of intestine which their results +1.75 , +3, +4with mortality rate 0%,10%,20% for vaccinated ,salinomycine treated &control groups respectively then took samples for Histopathologicalchanges the results pointed high pathological changes in intestine ofpositive control group with sever necrosis & degeneration of epitheliawith sever tissue damage companied with maturation first & secondgeneration sporozoite in the endothelial layer of intestine. While thepathological changes was less sever in salinomycine treated group withnecrosis & degeneration of epithelial layers accompanied with exist ofsporozoite in endothelial layer of intestine . while the vaccinated groupshowed no clear pathological changes in intestine except hyperplasia ofglobal cells & infiltration of lymphocytes cells in the layers of intestine ,it was concluded that the vaccine which was given to chicks provide goodprotection & decrease dangerous of coccidiosis infection .